Dinâmica do sistema binário Plutão-Caronte - Santos, Pryscilla Maria Pires dos [UNESP] (2014)
In this work, we investigate the orbital evolution of the escaping dust from both small satellites of Pluto: Nix and Hydra, produced via impacts of micrometeoroids on the surfaces of the small satellites, under the influence of the solar radiation pressure combined with the gravitational ejects of Pluto, Charon, and the parent-bodies (Nix and Hydra). The mass production rate of micron-sized dust particles is obtained and numerical simulations are performed to derive the lifetime of the ejecta. The ejected particles form a wide ring of about 16,000 km, which corresponds to the radial distance between the orbits of Nix and Hydra. Through the numerical simulations we verified that collisions with the massive bodies within the system and escape into hyperbolic orbits are the main mechanisms of loss of material, which are mainly determined by the solar radiation pressure acting on the grains. This important loss mechanism removes 30% of the initial set of 1 µ sized particles in 1 year. The surviving particles form a ring too faint to be detectable with a derived maximum optical depth of 4x10¹¹. We also explore the possibility that the progenitors of the small satellites of Pluto have been captured by the Pluto-Charon binary from the massive heliocentric planetesimal disk in which Pluto was originally embedded into. Wend that debris with small approximation velocities to the binary can be captured temporarily by Pluto-Charon with non-negligible probability, due to the dynamical perturbations exerted by the binary nature of the Pluto-Charon pair... (Complete abstract click eletronic access below)